Automatic vision-guided robotic cell micromanipulation system - Zhang, Yanliang (2010)
In life science research and applications such as cell mechanobiology, cell micromanipulation is skill-intensive, involving cell immobilization, micropipette positioning, cell biomembrane deformation and penetration, etc. The imprecise and inconsistent positioning in manual cell micromanipulation and biomembrane stress control demands a vision-guided robotic system to achieve high-accuracy static position control and dynamic motion tracking. This dissertation emphasizes the various techniques in realizing the aforementioned system.